Apomorphine and levodopa in Parkinson's disease: Two revolutionary drugs from the 1950's. (December 2016) - Djamshidian, Atbin; Poewe, Werner
Abstract: This article reviews the history of apomorphine and levodopa, which were both discovered in the 1950's and have revolutionized treatment paradigms of Parkinson's disease. Although the discovery of levodopa is a prime example of successful translation of basic neuroscience into clinical routine, the history of apomorphine was based on less solid evidence. Despite this, both drugs are, more than 6 decades after the first clinical experiments, still the two most efficacious medications to treat patients with Parkinson's disease. New and promising delivery strategies for both levodopa and apomorphine are currently under investigation to further improve clinical responses. Highlights: No other currently available drug can match the efficacy of apomorphine or levodopa. Both, apomorphine and levodopa were initially met with scepticism. Even today novel formulations of both drugs are currently under investigation.